Female Genital Mutilation : obstetric outcomes and perceived health consequences among women affected - Bita Eshraghi (2025)
BackgroundFemale Genital Mutilation (FGM) involves the partial or total removal of the external female genitalia for non-medical reasons and is associated with serious health risks. The growing number of women from countries where FGM is practiced presents new challenges for healthcare systems in receiving countries. To improve care and promote health equity, it is essential to increase understanding of both the obstetric complications associated with FGM and the healthcare experiences of affected women.AimThis thesis aimed to investigate how FGM affects obstetric outcomes with a particular focus on obstetric anal sphincter injury (OASI) and emergency cesarean section (CS), and to explore the lived experiences of women with FGM and their experience of healthcare encounters in Sweden.Material, methods and resultsThe first study was a nationwide cohort study including 187 738 primiparous women with singleton term vaginal births in Sweden (2014-2018). It showed that women with a registered FGM diagnosis (n=1 444) had a nearly threefold increased risk of OASI (OR 2.69, 95%CI: 2.14-3.37) compared to women without FGM diagnosis (n= 186 294). FGM was also associated with a higher rate of instrumental deliveries and episiotomy.The second study was a qualitative interview study with eight women living in Sweden who had undergone FGM prior to migration. This study highlights the complexity of FGM, revealing a wide range of experiences and perceived health consequences among women affected. Additionally, women reported inadequate knowledge about FGM, disrespectful attitudes, and insensitive care when seeking healthcare, though some also reported positive encounters.The third study was a nationwide cohort study (2014-2020) that included 229 026 births and examined the risk of emergency CS for women born in FGM- practicing countries (n= 14 602) compared to women born in Sweden (n= 214 424). Women from FGM-practicing countries had a higher risk of emergency CS (aOR 1.23, 95% CI: 1.17-1.30) compared to Swedish-born women. However, when adding FGM diagnosis as a covariate in the regression model, FGM diagnosis did not change the risk.ConclusionsIn our study, women with FGM had an increased risk of OASI when having a vaginal delivery in Sweden. The increased risk of emergency CS among women from FGM- practicing countries appears to be attributed to factors other than the FGM diagnosis itself. Increasing healthcare providers' knowledge about obstetric complications associated with FGM is essential to ensure optimal care and prevent adverse obstetric outcomes. Since women affected by FGM perceive their health consequences in various ways, it is further important for healthcare professionals to acknowledge the diversity within this group. Adopting a sensitive, individualized approach and improving healthcare providers' understanding of FGM is key to enhancing women's experiences and perceptions of care.List of scientific papersI. Eshraghi B, Hermansson J, Berggren V, Marions LRisk of obstetric anal sphincter tear among primiparous women with a history of female genital mutilation, giving birth in Sweden. PLoS One. 2022 Dec 17(12): e0279295. https://doi.org/10.1371/journal.pone.0279295II. Eshraghi B, Marions L, Berger C, Berggren V."A part of my life". A qualitative study about perceptions of female genital mutilation and experiences of healthcare among affected women residing in Sweden. BMC Women's Health. 2024 May 22;24(1):304. https://doi.org/10.1186/s12905-024-03149-1III. Eshraghi B, Hermansson J, Marions L.Risk of emergency cesarean section when giving birth in Sweden. A nationwide cohort study comparing women born in countries practicing female genital mutilation, with Swedish-born women. [Submitted]